Corporate social responsibility in countries with mature and emerging pharmaceutical sectors - Sax S; Anderson S; Volodina A (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
In recent decades the concept of Corporate Social Responsibility (CSR) has been adopted by many business sectors, including the pharmaceutical industry. However, in this and other sectors its application remains variable, particularly between mature and developing economies. Its stakeholders include pharmacy and medical students, their attitude to the involvement of companies in socially responsible activities will be important determinants of public response to the industry.Objective: To investigate the knowledge, attitudes and practices of senior medical and pharmacy students towards the CSR concept in the pharmaceutical sector in mature (Germany) and developing (Russia) markets. Methods: A questionnaire survey was carried out among senior pharmacy and medical students during the summer semester 2008 in two Russian and one German university. In each country 120 questionnaires were distributed. The response rate was 95% in Russia and 93% in Germany. Results: Although the relevance of CSR was widely acknowledged by the students, very few were aware of CSR practices currently performed by companies. The reputation of the pharmaceutical industry was generally poor: less than 15% of respondents gave credence to the information provided in advertisements and fully supported pricing strategies as well as policies towards the developing countries. When choosing an employer more than 90% of respondents consider the policies affecting an employee directly as pivotal. However, for a high proportion of students (59% in Russia and 64% in Germany) socially irresponsible behavior by companies has a significant negative impact. Conclusions: This paper identifies practices which students believe should be a part of the CSR programmes for the pharmaceutical industry, and also some that should be abandoned. It recommends that corporate communication on CSR should be expanded. Key differences are seen in perceptions of students in Germany and Russia towards the extent of irresponsible actions and the variation between them.